2017
DOI: 10.1177/1178224217719441
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Journey Mapping to Create a Palliative Care Pathway in a Canadian First Nations Community: Implications for Service Integration and Policy Development

Abstract: Providing palliative care in Indigenous communities is of growing international interest. This study describes and analyzes a unique journey mapping process undertaken in a First Nations community in rural Canada. The goal of this participatory action research was to improve quality and access to palliative care at home by better integrating First Nations’ health services and urban non-Indigenous health services. Four journey mapping workshops were conducted to create a care pathway which was implemented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…The interviews were recorded and transcribed by the interviewers. Text was imported into HyperRESEARCH software (©ResearchWare Incorporated) and a summative content analysis was undertaken [17]. Text was coded according to units of meaning (words and phrases), first within data for each participant and subsequently across participant categories.…”
Section: Discussionmentioning
confidence: 99%
“…The interviews were recorded and transcribed by the interviewers. Text was imported into HyperRESEARCH software (©ResearchWare Incorporated) and a summative content analysis was undertaken [17]. Text was coded according to units of meaning (words and phrases), first within data for each participant and subsequently across participant categories.…”
Section: Discussionmentioning
confidence: 99%
“…Data emphasized the need for better communication and social support/care.External heath care providers who provided care in the community were invited to participate in a journey mapping event to create the palliative care pathway for home care. Evaluations indicated that through journey mapping they learned how the community provides care in the First Nation, what local health service available, and how to integrate their services in a culturally appropriate way [43]. External heath care providers were invited to participate in full day cultural awareness workshops hosted by the First Nations community.…”
Section: Resultsmentioning
confidence: 99%
“…Policy recommendations were created for health care decision makers. Research outcomes can be found in publications [1, 4346], community reports [47–50], and a workbook for other First Nations communities entitled “Developing Palliative Care Programs in First Nations Communities” [51]. This paper by the EOLFN researchers adds new data on education to the existing dissemination.…”
Section: Introductionmentioning
confidence: 99%
“…Similar positive results around increasing communication and establishing partnerships were found by another study that focused on using journey mapping to engage a First Nation community in Canada to better communicate their needs to health providers. 35 Additional evidence is needed to supplement these journeys in order to turn interest into action, but the journeys provide an accessible entry point to discussion.…”
Section: Discussionmentioning
confidence: 99%